Frequency of family support of older rural Malaysian - Wan Ahmad, Wan Ibrahim (International digital organization for scientific information (IDOSI), 2014)
Population aging has become a challenge not only for developed countries but developing ones as well.Malaysia is being no exception.The purpose of this paper is to analyze the frequency of family support of older citizens in rural Malaysia. The design used in this study was a combination of the sociological method of face-to-face interviews and the anthropological method of participant observation.Analysis on the frequency of support shows that the frequency of support the elderly receive was varies.The analysis reveals that, out of 214 respondents, 20.2% reported they did not receive any support at all from family. From 79.8% of the elderly who receives support from family, 53.0% receive it once in a while and 26.8% receive it always in three weeks before the study. There were kinds of support the elderly received in almost every day, while others the elderly respondents only received once in a while.From the number of respondents who receive support shows that the welfare of older persons in rural community is not abandoned.